Analysis of the Quality, Nutritional and Supplementary Food Shelf Life Ation (Mp-ASI), Which in Substiusi with Flour Catfish (Clarias Gariepinus) and Pumpkin Flour (Cucurbitha Moschata) - Sri Darningsih; Iswanelly Mourbas; Ismanilda (proceedinginternational, 2023)
Malnutrition in infants will cause growth and development problems, if not addressed early can continue into adulthood. Age 0-24 months is a period of rapid growth and development, or also known as the golden period as well as a critical period. The golden period can be realized if during this time infants and children obtain appropriate nutritional intake for optimal growth and development.1 Provision of nutrient-dense and safe food for infants as complementary foods (AS-ASI) should be given from the age of six months. Babies need additional energy by 24-30% because the nutritional content of milk is not sufficient. One of the local food sources of protein that can be used as MP-ASI material is catfish (Clarias gariepinus). Catfish is a freshwater fish that is easily found and has a protein content of 68.6%. The purpose of this study is to determine the nutrient content, both in mocrobiology and chemistry as well as the shelf life of MP-ASI instant baby porridge with the substitution of catfish flour and pumpkin flour. This research is a continuation of previous research. Type of experimental research, descriptive data processing. Results: The best assessment results in the first stage of 2018 were Formula A, namely substitution of 15% catfish flour, 10% Pumpkin flour. The results of the quality and microbiology tests obtained were tests of water content, ash content, metal contamination and microbiological tests of MPASI pulp substituted with catfish flour and yellow pumpkin flour were within the standard limits of the instant MPASI SNI set by the Government. The nutritional value of MPASI is in the range of SNI 01-7111-1-2005 and the shelf life of MPASI has been up to five months. There are no signs of organoleptic damage to the color, taste, aroma of the porridge both stored at room temperature and stored in the refregerator. It can be concluded that MPASI porridge substituted with catfish flour and pumpkin flour is safe for consumption by babies 6-12 months, has good nutritional value and can be used as an alternative food to prevent malnutrition and stunting. It is recommended that this MPASI be used for handling infants who are experiencing acute malnutrition both at the Posyandu and at the Puskesmas as Supplementary food to Babies from local food. Further research needs to be given to infants aged 6-12 months, and see changes in body weight.